Troxler Fading, Eye Movements, and Retinal Ganglion Cell Properties. (December 2014) - Bachy, Romain; Zaidi, Qasim
We present four movies demonstrating the effect of flicker and blur on the magnitude and speed of adaptation for foveal and peripheral vision along the three color axes that isolate retinal ganglion cells projecting to magno, parvo, and konio layers of the LGN. The demonstrations support the eye movement hypothesis for Troxler fading for brightness and color, and demonstrate the effects of flicker and blur on adaptation of each class of retinal ganglion cells.